2016
DOI: 10.1080/02640414.2016.1244352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of consecutive days of match play on technical performance in tennis

Abstract: Elite tennis is characterised by repeated bouts of up to 5-set match play, yet little is known about the technical requirements of shots played. This study therefore investigated technical performance changes over consecutive days of prolonged, simulated tennis match play. A total of 7 well-trained men tennis players performed 4 consecutive days of competitive 4-h match play. Matches were notated to determine between-day changes in groundstroke and serve performance, as well as point and match durations. Chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…For example, females have slower movement speeds15 and lower absolute strength16 compared with professional male tennis players. Therefore, they may have less time to set up for optimal stroke execution resulting in compromised joint positioning 17. This could explain their high prevalence of injuries across both extremities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, females have slower movement speeds15 and lower absolute strength16 compared with professional male tennis players. Therefore, they may have less time to set up for optimal stroke execution resulting in compromised joint positioning 17. This could explain their high prevalence of injuries across both extremities.…”
Section: Discussionmentioning
confidence: 99%
“…These data confirm the outcomes which emerged from O' Donoghue and Liddle (1998), in which the average duration of a tennis match is about 90-120 min on grass or concrete and from 120 to 180 min on clay. Nevertheless, the technical-tactical evolution of recent years has led to more similar playing times on both hard and clay courts (Fabre, Martin, Gondin, Cottin, & Gerlot, 2012 a result of the frequent active and passive recovery periods, the average effective playing time corresponds to 24% of the total (Christmass, Richmond, Cable, Arthur, & Hartmann, 1998;Botton, Hautier, & Eclache, 2011;Smekal et al, 2001) and it further decreases after the third consecutive day of match play (Gescheit et al, 2016). The average duration of rallies is about 5 s (Smekal et al, 2001;Botton et al, 2011), whereas 56% of them last from 1 to 6 s and 18% from 6 to 9 s (Mendez-Villanueva, Ferandez-Fernandez, Bishop, FernandezGarcia, & Terrados, 2007), with an average of 2 s of rest per each second of work (Christmass et al, 1998;Murias et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this characteristic determines that the building, interpreting and eventually predicting players' performance should be done acknowledging the variability of the game and different types of players (Butterworth, O'Donoghue, & Cropley, 2013). In the present, some studies attempted to explore the issue of variability by, for example, analyzing the players' physical and technical performance variation during consecutive days of simulated matches (Gescheit et al, 2015;Gescheit et al, 2016). However, the practical inferences were limited as they were not based on real matches.…”
Section: Limitation and Issues Of Current Investigationmentioning
confidence: 99%
“…Contrary to the expectation, most existing literature exclusively focused on reporting the general match performance of players (Ma et al, 2013;Reid et al, 2016), failing to evaluate how different technical, tactical and physical variables were influenced within prolonged time or days as tennis is played as a tournament format. In light of this issue, several studies have attempted to assess how well-trained players' physiological and technical performance were influenced during simulated tournament that lasted 3 to 4 days with a match duration of 2 to 4 hours (Gescheit et al, 2015;Gescheit et al, 2016;Ojala & Häkkinen, 2013). Results of these studies were informative and showed that their technical, physical, physiological and perceptual status were compromised over consecutive days of the tournament due to heavy speed strength load, muscle damage, and neuromuscular and perceptual fatigue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation